Vibration Analysis of Composite Laminated Plates Using Analytical and APDL ANSYS Codes - Lanja Saeed Omer; Safeen Yaseen Ezdeen (QALAAI ZANIST JOURNAL, 2022)
The aim of this work is to investigate analytical (Classical theory) and [ANSYS Parametric Design Language (APDL)] analysis of laminate composite plate. The free vibration analysis with two boundary conditions simply supported (SSSS) & clamped ends (CCCC) are taken into account in this work. The equations of motion that governs the predication of dynamic behavior of cross and angle ply composite are solved theoretically using [Matlab] software. Three degrees of freedom are included in computing the natural frequency and mode shapes of cross and angle ply laminate. The significant effect of various parameters such as number of layers of fibers, aspect ratios, fiber orientation, and modulus ratio on natural frequency is evaluated theoretically and APDL (ANSYS). The numerical analysis is carried out by commercially available ANSYS software. The boundary conditions can significantly affect the natural frequency of the composite laminate plate due to the restraint effect at the edges. In this work a relatively new modeling technique will be adopted. Good agreement is achieved between the analytical and ANSYS results.